Adhesion of Stenotrophomonas maltophilia to Biotic and Abiotic Surfaces and Role of Flagella in Bacterial Adhesion (World Journal of Experimental Biosciences, 2022)
The bacterial adhesion to the biotic and abiotic surfaces represents the first step in infection and contributes to increasing the pathogenicity of bacteria. In the current review, we have shed light on the ability of Stenotrophomonas maltophilia to adhere to biotic and abiotic surfaces and the role of this adhesion in increasing the virulence of this bacteria and its ability to cause infectious diseases. The adhesion of S. maltophilia to abiotic surfaces contributes to the bacteria’s resistance to the wild spectrum of antibiotics in addition to evading the body’s immune response during biofilm formation. Bacterial appendages such as flagella and pili play an important role in adhesion to biotic and abiotic surfaces. Studies have shown the role of the flagella of S. maltophilia in adhesion to biotic and abiotic. The current study also showed the role of pili of S. maltophilia and bacterial outer membrane proteins in adhesion to the surfaces. The adhesion of bacteria to biotic surfaces occurs through the attachment of bacterial appendages to receptors located on the surfaces of living cells. The mechanism adopted by S. maltophilia to adhere to biotic surfaces is through binding to specific receptors on the surface of living cells or by attaching to mucus, especially in the respiratory tract. As for adhesion to abiotic surfaces, it depends on the hydrophobic forces as well as the electrical charges and the van der Waals force. Adhesion of S. maltophilia to the surfaces is considered one of the mechanisms used by bacteria to resist antibiotics and cause infectious diseases. The increased ability of S. maltophilia to adhere to surfaces has contributed to the increase in the pathogenicity of this bacteria in recent years.